2010
DOI: 10.1021/ja107876p
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Reorganization Free Energies for Biological Electron Transfer: A Comparative Study of Ru-Modified Cytochromes and a 4-Helix Bundle Protein

Abstract: The acceleration of electron transfer (ET) rates in redox proteins relative to aqueous solutes can be attributed to the protein's ability to reduce the nuclear response or reorganization upon ET, while maintaining sufficiently high electronic coupling. Quantitative predictions of reorganization free energy remain a challenge, both experimentally and computationally. Using density functional calculations and molecular dynamics simulation with an electronically polarizable force field, we report reorganization f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
135
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(152 citation statements)
references
References 48 publications
13
135
0
Order By: Relevance
“…It is often assumed or observed that the solvent dominates the outer-sphere RE, 15,18 although this not the case for all proteins. 105 In our case, for which there is no change in the net charge of the protein, the solvent contribution to the RE is rather small. Many residues contribute to the protein term, all providing rather small contributions.…”
Section: Reorganisation Energies From the MD Simulationsmentioning
confidence: 54%
See 2 more Smart Citations
“…It is often assumed or observed that the solvent dominates the outer-sphere RE, 15,18 although this not the case for all proteins. 105 In our case, for which there is no change in the net charge of the protein, the solvent contribution to the RE is rather small. Many residues contribute to the protein term, all providing rather small contributions.…”
Section: Reorganisation Energies From the MD Simulationsmentioning
confidence: 54%
“…Our simulations show that this is a reasonable assumption, as can be seen in Figure 6. The parameters  and  Finally, the reorganisation energy can also be calculated directly from  2 2RT , 15,105 which gives 124 and 114 kJ/mol for the OR and RO simulations, respectively. Some further understanding of the RE can be obtained by dividing the results from Eqn.…”
Section: Reorganisation Energies From the MD Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical MD simulations were carried out with the the AMBER03 protein force field (36) together with the TIP3P water model (37). Force field parameters for the heme cofactors were taken from earlier work (32,38,39).…”
Section: Methodsmentioning
confidence: 99%
“…But QM/MM approaches that model intramolecular electron transfer in a manner that parallels Marcus theory may prove valuable in moving to this goal. [71][72][73] …”
Section: Electrochemical Potential As a Determinant Of Electron Flux mentioning
confidence: 99%